Repeated high-intensity exercise in professional rugby union - Austin, D.; Gabbett, T.; Jenkins, D. (Journal of Sports Sciences, 2011)
The aim of the present study was to describe the frequency, duration, and nature of repeated high-intensity exercise in Super 14 rugby union. Time-motion analysis was used during seven competition matches over the 2008 and 2009 Super 14 seasons; five players from each of four positional groups (front row forwards, back row forwards, inside backs, and outside backs) were assessed (20 players in total). A repeated high-intensity exercise bout was considered to involve three or more sprints, and/or tackles and/or scrum/ruck/maul activities within 21 s during the same passage of play. The range of repeated high-intensity exercise bouts for each group in a match was as follows: 11-18 for front row forwards, 11-21 for back row forwards, 13-18 for inside backs, and 2-11 for outside backs. The durations of the most intense repeated high-intensity exercise bouts for each position ranged from 53 s to 165 s and the minimum recovery periods between repeated high-intensity exercise bouts ranged from 25 s for the back row forwards to 64 s for the front row forwards. The present results show that repeated high-intensity exercise bouts vary in duration and activities relative to position but all players in a game will average at least 10 changes in activity in the most demanding bouts and complete at least one tackle and two sprints. The most intense periods of activity are likely to last as long as 120 s and as little as 25 s recovery may separate consecutive repeated high-intensity exercise bouts. The present findings can be used by coaches to prepare their players for the most demanding passages of play likely to be experienced in elite rugby union.